Bitter leaf (Vernonia amygdalina Del) extract potentiates testicular metabolic stress induced by petroleum-tainted diets in rats - Achuba, F. I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The effect of hydrocarbon adulterated diets on male fertility has been of grave concern to researchers. This study evaluated the effects of bitter leaf methanol extract on petroleum-induced testicular damage. Rattus norvegicus species of albino rats were allotted into six sets. Each set composed six rats. The sets were defined as follows: Set A was rats fed Feed without any treatment; Sets B and C were given feed without treatment and measured doses of bitter leaf extract; Set D was fed unrefined petroleum tainted feed; Sets E and F were given tainted feed and doses of bitter leaf extract used in sets B and C, respectively. After the exposure period, testes were removed from sacrificed animals and clinical investigation carried out. Analysis of variance (ANOVA) was employed for data comparison. The results revealed that unrefined petroleum tainted diets meaningfully (P < 0.05) prompted testicular metabolic stress indicators, while significantly (P < 0.05) plummeting the antioxidant defense markers compared to control. Administration of bitter leaf extract was not able to ameliorate altered indices of stress but contributed to increase in testicular metabolic stress. The study concluded that bitter leaf enhanced testicular damage imposed by unrefined petroleum adulterated feed and may possibly have a noxious effect on the testes.